Implications of antibiotics use during the COVID-19 pandemic: present and future. (24th August 2020) - Miranda, Carla; Silva, Vanessa; Capita, Rosa; Alonso-Calleja, Carlos; Igrejas, Gilberto; Poeta, Patrícia
Abstract: COVID-19 is caused by the SARS-CoV-2 virus, which has infected more than 4 million people with 278 892 deaths worldwide as of 11 May 2020. This disease, which can manifest as a severe respiratory infection, has been declared as a public health emergency of international concern and is being treated with a variety of antivirals, antibiotics and antifungals. This article highlights the administration of antimicrobials in COVID-19 patients worldwide, during the 2019–20 pandemic. It is imperative to be aware of the unreported amounts of antibiotics that have been administered worldwide in just a few months and a marked increase in antimicrobial resistance should therefore be expected. Due to the lack of data about antimicrobial use during this pandemic, the global impact on the emergence of new antimicrobial resistance is as yet unknown. This issue must be at the forefront of public health policymaking and planning in order that we are prepared for the potentially severe consequences for human and animal health and the environment.